114k views
1 vote
Rearrange the equation so w is the independent variable.
u-5= -4(w - 1)

User Libor
by
4.8k points

2 Answers

7 votes

Answer:

w = ((u-5)/-4) + 1

Explanation:

To make w an independent variable, it must be by itself, so we have

u - 5 = -4(w-1)

We divide both sides by -4

(u-5)/-4 = -4(w-1)/-4

(u-5)/-4 = w-1

Now we add 1 to both sides,

(u-5)/-4+1 = w-1+1

((u-5)/-4) + 1 = w

w = ((u-5)/-4) + 1

User Jonathan Mayer
by
4.6k points
2 votes

Answer:

u = -4w + 9.

Explanation:

If w is the independent variable, it will be the variable you are changing.

u - 5 = -4(w - 1)

u - 5 = -4w + 4

u = -4w + 9.

Hope this helps!

User Tejas K
by
4.8k points